Türk borçlar hukukunda gayrimenkul tellallığı sözleşmesi - Şahiniz, C. Salih (My University, 2002)
TÜRK BORÇLAR HUKUKUNDA GAYRİMENKUL TELLALLIĞI SÖZLEŞMESİ Doktora tezimizde, Türk Borçlar Kanunu Hükümleri çerçevesinde gayrimenkul tellallığı sözleşmesi incelenmiştir. Gayrimenkul tellallığı sözleşmesi, Türk Borçlar Kanununun 404 ila 409'uncu maddeleri arasında düzenlenmiştir. Tellallık sözleşmesinin tanımına gelince: Tellallık öyle bir sözleşmedir ki, bununla müvekkil, tellalın gösterdiği fırsatın ya da yaptığı aracılığın bir esas sözleşmenin kurulması ile sonuçlanması şartına bağlı olarak tellala ücret ödemeyi borçlanır. Gayrimenkul tellallığına ilişkin incelememiz, bu müesseseyi oluşturan iki sözleşme çerçevesinde şekillenmiştir. Bunlar; müvekkil ile tellal arasında akdedilen tellallık sözleşmesi ve müvekkil ile üçüncü kişi arasında akdedilen esas sözleşmedir. Burada, esas sözleşmenin konusunu, bir gayrimenkul üzerinde şahsi veya ayni hak tesisi ilişkisi kuran her türlü sözleşme oluşturur. Müvekkil ile tellal arasında kurulan tellallık sözleşmesi ise, Borçlar Kanununda düzenlenmiş bulunan vekalet sözleşmesinin bir alt türünü oluşturmaktadır. Tezimiz iki ana bölümden oluşmaktadır. gayrimenkul tellallığı sözleşmesi başlığını taşıyan birinci bölümde şu konular incelenmiştir: -Gayrimenkul tellallığı sözleşmesinin tanımı, unsurları ve özellikleri -Tellallık sözleşmesinin hukuki niteliği -Vekalete ilişkin hükümlerin tellallıkta tali (ikincil) olarak uygulanması -Tellallık sözleşmesinin benzer hukuki ilişkiler ile karşılaştırılması ve gayrimenkul tellallığının ticaret işleri tellallığı ile ilişkisi -Tellallık sözleşmesinin kuruluşu ve şekli -Tarafların sözleşmeden doğan hakları ve borçları -Müvekkilin birden fazla tellalın faaliyetinden yararlanması ve bunun sonuçları -Sözleşmenin sona ermesi Tezimizin tellallık ücreti başlığını taşıyan ikinci bölümünde ise şu konular incelenmiştir: -Tellallık ücreti kavramı ve özellikleri -Ücretin miktarının tespiti -Ücretin indirilmesi -Tellalın masraflarının karşılanması -Tellalın ücrete hak kazanması için gerçekleşmesi gerekli olan şartlar -Tellallık ücretini garanti etmeye yönelik sözleşme kayıtları (ücret garantisi kayıtları) Gayrimenkul tellallığı sözleşmesi, uygulamada sıklıkla rastlanılan bir sözleşme türüdür. Böyle olmakla birlikte, ülkemizde, bu konuya ilişkin herhangi bir monografik eser bulunmamaktadır. Tezimiz ile, bu konudaki önemli bir boşluğu kapatmayı amaçladık.

CONRACT OF PROPERTY BROKERAGE ACCORDING TO THE TURKISH LAW OF OBLIGATIONS In this PhD Dissertation, the contract of real property brokerage according to the Turkish Law of Obligations was examined. The contract of real property brokerage is regulated in between the article 404 and 409 of the Turkish Code of Obligations. The contract of Real Property Brokerage is such a contract that with this contract the mandator has the obligation to make a payment to the broker as a consideration related to the condition of the forming a main contract as a result of indication of the broker or the negotiation that he has performed. Our thesis is mainly focused on two contracts that combine in order to create the contract of real property brokerage. These are: the contract that is formed between the mandator and the broker (contract of brokerage), and the second contract is the contract in between the mandator and the third party (the main contract). The subject of the main contract is about all sorts of contracts related to the foundation of a real or a personel right on the real property. The other contract that is concluded in between the mandator and the broker, is a sub contract of the contract of mandate that is regulated in The Turkish Code of Obligations. Our Thesis is made up of two sections. These titles were examined in the first section: -The descriptions, the elements and the specialities of the Contract of Real Property Brokerage -The legal aspects of the Contract of Real Property Brokerage -The subsidiary application of the articles related to the Contract of Mandate -The comparison of the Contract of Real Property Brokerage with the similar legal transactions and the relations with the commercial brokerage -The formation and the legal form of the Contract of Real Property Brokerage -The rights and obligations of the parties arising from the Contract of Real Property Brokerage -The utilization of more than one broker by the mandator and its results -The termination of the Contract In the second section the titles mentioned below were examinated: -The fee of the Broker and its specialities -The determination of the amount of the fee -The decrease of the fee by the Judge -The payment of the expenses of the broker -The conditions that have to be met in order to maintain a right to get the fee -The closes of guarantee of the fee The Contract of Real Property Brokerage is a contract that one meets so often in judicial life. However, in Turkey no monographic examination on this issue was written beforehand. Therefore, our Thesis is the first legal attempt in this empty field which has to be comleted immediately.
Keywords: Borçlar Hukuku Türkiye; Gayrimenkul Yatırımları; Hukuk; Özel Hukuk; Ticaret hukuku